Characteristic Signal of FT3 Measuring Probe - Vit, Jiri; Novak, Martin (Manufacturing Technology Journal, 2019)
The article deals with the determining of the characteristic signal of the inductive FT3 measuring probe, that is used on the roundness machines of Jenoptik IM producer. The research was the basis for generalized recommendations for the calibration of the probe, which was published in the article "A roundness machine measuring probe calibration". The signals of eight FT3 probes have been acquired and evaluated for repeatability and mutual equality. Five signals of each individual probe were taken immediately for repeatability evaluation. The deviations of the individual signals from the mean signal and the deviations of the signal first derivative curves from the mean first derivative curve have been evaluated for the repeatability evaluation. The deviations of the signal of the individual probes from the perfect signal have been evaluated for the equality evaluation.
Keywords: Matlab; probe signal; roundness machine